Unlocking potentials enhancing children’s cognitive development through the landscape spectrum matrix approach in Maybunga Rainforest Park, Pasig City - Cruz, Erwin J.; Bello, Jaclyn Alexandra Marie B.; Fontanoza, Franklin Jr. S. (Quezon City College of Architecture, University of the Philippines Diliman, 2024)
In the early 21st century, UNICEF recorded 200 million children in developing
nations, including the Philippines, lack expected cognitive development due to limited
early learning opportunities. This study focuses on childhood cognitive development,
emphasizing open spaces using the Landscape Spectrum Matrix Approach. It
highlights the current oversight in recognizing landscapes as essential for early
cognitive and behavioral growth. Aligned with the United Nations' Sustainable
Development Goals: Good Health and Wellbeing, the study underscores the vital role
of open spaces in children's development. The World Health Organization recognizes
the continuous brain development in children, emphasizing the importance of early
experiences in shaping lifelong learning, health, and behavior. The Philippines,
through the Early Childhood Care and Development (ECCD) Council, has various
initiatives for childhood well-being. However, this study finds a significant gap in
understanding the potential of outdoor spaces for childhood development. The
methodology includes data gathering through site inventory, interviews, workshops,
and observation, with the Landscape Spectrum Matrix Approach utilized in the study.
Findings reveal four main elements: Playful and Comfort Elements, Sports-related
Activities/Coordination Skills in Play, Visual Engagement and Creativity in Play, and
Nature-inspired Elements and Positive Imagery (Sensory Stimulation). The design
integrates intelligence traits across three zones: Playful Learning, Adventure
Exploration, and Nature Contemplation, each offering different play environments
within the concrete operational stage of children’s cognitive development. The study
concludes that incorporating these elements into outdoor spaces can significantly
enhance childhood cognitive development.
Include appendices
Thesis (Bachelor of Landscape Architecture) -- University of the Philippines Diliman
Keywords: Open spaces -- Pasig City; Child development -- Pasig City; Cognition in children -- Pasig City; Landscape design -- Pasig City